REVIEW JURNAL: PENGARUH PENERAPAN MEDIA POWERPOINT TERHADAP HASIL BELAJAR IPAS SISWA KELAS VI SEKOLAH DASAR : ANALISIS UJI-T - Batubara, Juliani; Insani, Hainur; Amir, Almira (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
ABSTRACT This research was conducted to examine the impact of PowerPoint-based instructional media on the learning outcomes of sixth-grade students in Natural and Social Sciences (IPAS) at SDN 200507 Pijorkoling. A quantitative approach was employed using a pre-experimental One Group Pretest–Posttest Design. The participants consisted of 11 students, including 5 males and 6 females. Data were collected through a multiple-choice achievement test administered before and after the instructional intervention. The data analysis revealed a statistically significant difference between pretest and posttest results, with the mean score increasing from 61.45 to 70.45. The results of the t-test indicated a significant effect (p = 0.000 < 0.05), demonstrating that the use of PowerPoint media significantly influenced students’ learning outcomes. Nevertheless, the N-Gain value of 0.2478 suggests that the level of improvement falls within the low effectiveness category. These findings indicate that while PowerPoint media contributes to a statistically measurable improvement in learning outcomes, its practical effectiveness requires further optimization. Keywords: PowerPoint, learning outcomes, IPAS, instructional media, elementary school students